PENJELAJAHAN MARWAH GORGA DALAM KARYA FILM DOKUMENTER BUDAYA DARI BUMI BATAK - Reynaldo Apriasie Sinaga; Enok Wartika; Retno Dwimarwati (LAYAR: Jurnal Ilmiah Seni Media Rekam, 2020)
Documentary film is a visualization of facts and reality. The film is packaged based on a team's research either done in depth or just a surface study. However, the contribution of field data is one of the strengthens that proves the quality of a documentary film. Documentary film "Marwah Gorga from the Batak land", is one of the movies based on in-depth research. The problem raised in this research is, how to study and visualize the aesthetic of gorga ornament, its meaning and correlation with homeowners on Samosir Island. The research method used is qualitative. The results show that there is a strong correlation between ornament and homeowner, and the spirit of gorga has a symbolic meaning that is respected by the people on Samosir Island. The charm and symbolic meaning of Gorga ornament can be visualized beautifully in the documentary film "Marwah Gorga from the Batak Land".